Volume changes under strain resulting from the incorporation of rubber granulates into a rubber matrix - Kumar, P; Fukahori, Y; Thomas, A.G; Busfield, J.J.C (Journal of polymer science. Part B, Polymer physics, 2007)
The strength of an elastomer is in part determined by the size of the intrinsic flaws that are present. It has been observed that the incorporation of rubber granulates into a virgin matrix results in a reduction in strength and this has previously been attributed to an increase in the intrinsic flaw size. The precise nature of this intrinsic flaw is the subject of this investigation. Fundamental questions concerning the change in flaw size with strain and the reduction in strength resulting from a weaker interface have been investigated using volume change experiments. Initial experiments on carbon black filled rubber with no granulates incorporated have shown no significant volume change under strain. This contrasts with granulate filled materials whose experimentally measured volume changes with strain were seen to be substantially greater. Microstructural finite element analysis has revealed how this change in volume might result from a net increase in the flaw size with increasing strain. This work suggests that flaw size increases in a characteristic way with strain for materials where the matrix and granulates have a similar modulus, whereas a modulus mismatch between the matrix and the recycled granulate results in much larger volume changes and hence greater flaw size which also appears to increase with strain. This work emphasizes the importance in practical applications of matching the modulus of recycled granulate materials to that of the new virgin material in the matrix. This article introduces a novel technique for examining small changes in the interfacial bonding mechanisms under strain such as that caused by surface modification techniques. © 2007 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 45: 3169-3180, 2007